2020
DOI: 10.1177/2158244020925501
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Supervision and Teachers’ Performance and Attitude in Secondary Schools in Malaysia

Abstract: This study was carried out to determine the relationships between supervision and teachers’ performance and attitude in secondary schools in Kuala Lumpur, Malaysia. This is a quantitative study where the 5-point Likert-type-scale questionnaire was used to analyze data using descriptive and inferential statistics. Simple random sampling was used to select the respondents. This study entailed respondents from various schools in one of the districts in Kuala Lumpur which comprises 200 teachers and 50 supervisors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 24 publications
6
55
1
7
Order By: Relevance
“…In this dimension, supervisors were tasked with providing motivation, support, and direction in order to help teachers grow more professionally and independently (Directorate General of Teachers and Education Personnel, 2016;Sudjana, 2012). This is in line with an opinion put forward by Brunelle et al (Hoque et al, 2020) that academic supervision aims to make teachers autonomous in running their teaching and learning processes. However, not all teachers are ready, this depends on their personal maturity and professionalism.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this dimension, supervisors were tasked with providing motivation, support, and direction in order to help teachers grow more professionally and independently (Directorate General of Teachers and Education Personnel, 2016;Sudjana, 2012). This is in line with an opinion put forward by Brunelle et al (Hoque et al, 2020) that academic supervision aims to make teachers autonomous in running their teaching and learning processes. However, not all teachers are ready, this depends on their personal maturity and professionalism.…”
Section: Discussionsupporting
confidence: 90%
“…Several research results showed that supervisors' support for the teaching and learning processes has a significant relationship with teachers' attitudes towards supervisors (Daud et al, 2018;Khumaedi, 2012;Ryan & Gottfried, 2012). It was further stated by Kazi, et al, (Hoque et al, 2020) that in an effort to improve the quality of teaching, supervision can be used as a strategy that allows teachers to achieve high quality learning goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervision must be able to help and solve the problems experienced by the teacher (Altunay, Arlı, Öz, & Yalçınkaya, 2013). Supervision is an effort to improve teaching, including stimulating, selecting job growth and teacher development, and revising educational goals, teaching materials and teaching methods, and evaluations (Hoque., et al, 2020.…”
Section: Supervise Of the Principalmentioning
confidence: 99%
“…Teacher performance is the ability and success of the teacher to carry out learning. There is a significant effect of teacher performance on teacher teaching abilities [12], [31]. Teacher performance can be seen through several indicators 1) ability to compile lesson plans; 2) the ability to carry out learning; 3) the ability to do interpersonal relationships; 4) ability to assess learning outcomes; 5) ability to carry out enrichment programs; 6) ability to implement improvement programs [33].…”
Section: Teacher Performancementioning
confidence: 99%